ANALISIS PENGENDALIAN PERSEDIAAN TEPUNG TERIGU DAN GULA PASIR MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY PADA ANEKA SARI BAKERY DI KARANGPANDAN - Bagus Ardyan Waskitanto; Amin Wahyudi; Sunarso Sunarso (Universitas Slamet Riyadi, 2020)
The purpose of this study is to analyze the efficiency of controlling raw material inventories using the Economic Order Quantity method compared to the conventional methods of the company today. Raw materials are important in the production process, therefore the company must have sufficient raw material supplies to support production activities. If the supply of raw materials owned is lacking, the production process will be hampered. The inhibition of the production process will affect the amount of output produced. If the output results cannot meet consumer demand, the amount of profits the company will receive will also decrease, even the company's trust will also decrease. Aneka Sari Bakery is a company engaged in the food industry. In food industry companies, the production process is an activity that is very important for the survival of the company. Inventory is one of the things that must be considered in a production process because it directly affects the smoothness of the production process.